2022
DOI: 10.1177/21582440221082131
|View full text |Cite
|
Sign up to set email alerts
|

Female Managers and Corruption in SMEs: A Comparison Between Family and Nonfamily SMEs in Vietnam

Abstract: Empirical evidence, regarding the impacts of female leadership on firm’s corrupt level, is lack of studies in various research context. The objective of this study is to assess whether female managers impact negatively or positively on the corrupt behavior of family SMEs (household business) and nonfamily SMEs (Small and Medium-sized Enterprises). To do that, this paper used regressions, taken from a sample of 1,720 Vietnamese SMEs (based on the survey data of UNU-WIDER), to compare the impact of female percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 128 publications
(185 reference statements)
0
3
0
Order By: Relevance
“…For example, females are ethically sensitive (Dawson, 1997; Eagly & Johnson, 1990) and less accepting of unethical practices in working place than their male peers (Larrieta‐Rubín de Celis et al, 2015; Liu, 2018). Furthermore, it is found that female directors and managers have a more positive attitude toward firm's ethical code of conduct (García‐Sánchez et al, 2015), and are less involved in unethical practices such as bribes (Tran et al, 2022). This leads female decision‐makers to have a positive impact on non‐profit‐making activities such as environmental issues and protect businesses from environmental risks as well as prevent negative business practices.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…For example, females are ethically sensitive (Dawson, 1997; Eagly & Johnson, 1990) and less accepting of unethical practices in working place than their male peers (Larrieta‐Rubín de Celis et al, 2015; Liu, 2018). Furthermore, it is found that female directors and managers have a more positive attitude toward firm's ethical code of conduct (García‐Sánchez et al, 2015), and are less involved in unethical practices such as bribes (Tran et al, 2022). This leads female decision‐makers to have a positive impact on non‐profit‐making activities such as environmental issues and protect businesses from environmental risks as well as prevent negative business practices.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…Corruption happens in enterprises, but enterprises also play a crucial role in much of the corruption that occurs in society, and they are also essential contexts for corruption themselves [43]. Some studies have linked gender and corruption, for instance, the perceptions about corruption by the female managers and owners of firms [44], the impact of corruption on applying for credit between female and male entrepreneurs [45], gender differences in enterprise-level bribery [46], women's moral standards and bribing [47], corruption in family SMEs and nonfamily SMEs [48], corrupt institutional environment and public subsidies for credit access by SMEs helmed by female entrepreneurs [49], the gendered effects of corruption on credit access and credit constraints [47], and gender and bribe paying [50]. As women form a considerable proportion of the informal sector, which is highly contaminated by corruption, there is a greater likelihood that they are under constant pressure to yield to corruption [51].…”
Section: Namibian Businesses and (In)equalitiesmentioning
confidence: 99%
“…For example, a minimum level rate of females on boards is required and implemented in some countries, such as Norway (40 %) and The Netherlands (30 %); however, this quota legislation is not applied in some developing countries, such as Vietnam. In the context of this country, compared to male colleagues, women have to overcome many obstacles to achieve a position in top management teams (TMTs), boards of directors or CEOs (Tran et al , 2022). There are several reasons for this.…”
Section: Introductionmentioning
confidence: 99%